Effects of immersion on young learners’ proficiency in Hong Kong - Edward Y. W. Chu; Xuyan Qiu (Cogent Education, 2025)
This quasi-experimental study was conducted in a Hong Kong primary school where the effects of an immersion programme on the English proficiency development of Grades 1–3 pupils were evaluated. Ninety-seven English-medium instruction (EMI) students and their 225 Chinese-medium instruction (CMI) peers completed pre-test and post-tests at the beginning and end of the academic year, respectively. Three administrators, six teachers, and one parent were interviewed regarding the programme’s effectiveness. Inferential statistical analyses were conducted to compare the pre-test and post-test results of the EMI and CMI groups, while the thematic content analysis was conducted to analyse the interview data. The quantitative results indicate that both EMI and CMI students improved their L2 (English) proficiency. The qualitative findings imply that the EMI group achieved this without compromising their first language (Chinese) and content subject learning. Different stakeholders attributed the effectiveness of immersion to student characteristics, teacher support, rich L2 resources, and parental involvement. The findings of this study provide pedagogical suggestions on the implementation of EMI for young learners.